2018
DOI: 10.1111/bjd.17202
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive and specific assay for the serological diagnosis of antilaminin 332 mucous membrane pemphigoid

Abstract: The novel IF-based assay will facilitate the serological diagnosis of antilaminin 332 MMP and may help to identify patients at risk of a malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 43 publications
7
72
0
2
Order By: Relevance
“…Serial IgG titres correlate with disease severity . Laminin‐332 is detected in up to 20% of patients, and is associated with more severe disease and solid organ tumours in up to 30% . Further testing with ELISA or immunoblotting studies may be undertaken.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Serial IgG titres correlate with disease severity . Laminin‐332 is detected in up to 20% of patients, and is associated with more severe disease and solid organ tumours in up to 30% . Further testing with ELISA or immunoblotting studies may be undertaken.…”
Section: Diagnosismentioning
confidence: 99%
“…12,13 Laminin-332 is detected in up to 20% of patients, and is associated with more severe disease and solid organ tumours in up to 30%. [14][15][16] Further testing with ELISA or immunoblotting studies may be undertaken. BIOCHIP Mosaics TM allow polyvalent immunofluorescence tests and provide antibody profiles in a single incubation.…”
Section: Diagnosismentioning
confidence: 99%
“…10 In a recent study by Goletz et al, IIF using recombinant laminin 332 was shown to be a valid assay for the diagnosis of laminin 332 MMP. 11 As rightly mentioned by Carey et al in their study, 1 DIF still represents the gold standard for establishing the diagnosis of both oral PV and MMP. In this regard, it is of critical importance to identify the mucosal area that is best suited for biopsy to increase the likelihood of positive DIF results being least invasive.…”
mentioning
confidence: 89%
“…reported increased sensitivity of indirect immunofluorescence (IIF) utilizing normal oral mucosa as a substrate instead of normal human skin or saline‐split human skin in 20 cases of oral MMP . In a recent study by Goletz et al ., IIF using recombinant laminin 332 was shown to be a valid assay for the diagnosis of laminin 332 MMP …”
mentioning
confidence: 99%
“…This may lead to faster remission of active disease and less scarring on the mucosa. Recently, a commercial biochip assay that detects antibodies to laminin‐332 has been tested, which also detects these autoantibodies . It would be interesting to compare the sensitivity and specificity of both of these assays.…”
mentioning
confidence: 99%